Book review: Zverev, Yu. M., & Mezhevich, N. M. (2024). Militarisation of Poland and Possible Responses of the Union State Within the Theory of Regional Security Complexes. Moscow: Izd-vo BFU im. I. Kanta publ., 126 p. (In Russian) - Maksim A. Nikulin (Vestnik RUDN. International Relations)
-